The Camden 28 - Giacchino, Anthony ([New York] : First Run Features, 2007)
In Camden, New Jersey, a group of 28 Vietnam War protesters plan to break into a local draft board office and destroy records during the summer of 1971. Little do they know that a mole has been planted in their group.
DVD.
Not rated.
Bonus materials: multiple interviews, bonus archive footage, the Camden 28 reunion, essay from Howard Zinn, filmmaker biographies.
Keywords: Vietnam War, 1961-1975 -- Protest movements -- New Jersey; Peace movements -- New Jersey